A study of economic importance for animal waste in Syrian coast - يعقوب, غسان; صبح, عادلينا (Latakia University Journal -Biological Sciences Series, 2021)
The research aimed first to estimate the quantity and value of animal production waste in Syrian coast, and second to present modern methods to benefit from them, relying on secondary data taken from the Ministry of Agriculture and Agrarian Reform, which then was analyzed using analytical and descriptive methods, and all calculations were performed using Excel program. The results of the research showed that the average of waste produced by farm animals during the period 2013-2017 was about 818.56 thousand tons. The quantities of biogas and organic fertilizer that can be produced from these wastes was estimated at 38.150 million cubic meters and 736.70 thousand tons, respectively.